Solitary vulvar metastasis from early-stage endometrial cancer: Case report and literature review. Issue 22 (4th June 2021) - Mandato, Vincenzo Dario; Mastrofilippo, Valentina; Palicelli, Andrea; Silvotti, Monica; Serra, Silvia; Giaccherini, Lucia; Aguzzoli, Lorenzo
Abstract: Rationale: Endometrial cancer (EC) is the most common gynecological malignancy in developed countries. It is usually diagnosed at early-stage and presents a favorable prognosis. Conversely, advanced or recurrent disease shows poor outcome. Most recurrences occur within 2 years postoperatively, typically in pelvic and para-aortic lymph nodes, vagina, peritoneum, and lungs. Vulvar metastasis (VM) is indeed anecdotal probably because of the different regional lymphatic drainage from corpus uteri. Patient concerns: A 3 cm, reddish, bleeding lesion of the posterior commissura/right labia was found in a 74-year-old woman treated with radical hysterectomy, surgical staging, and adjuvant radiotherapy 1 year before for a grade 2 endometrioid type, International Federation of Gynecology and Obstetrics Stage IB. Vulvar biopsy confirmed the EC recurrence. Pelvic magnetic resonance imaging and positron emission tomography excluded other metastases so VM was radically resected. Diagnosis: Postoperative histopathology confirmed the diagnosis of grade 2 EC VM. Interventions: A radical excision of VM was performed. Outcomes: Patient died from a severe sepsis 27 months after first surgery. Lessons: Vulvar metastases can show different appearance, occurring as single or diffuse lesions on healthy or injured skin. The surgical approach seems not to influence the metastatic risk, but tumor seeding and vaginal injuries should be avoided. Whether isolated or associated with recurrence in other locations, vulvar metastases imply poor prognosis despite radical treatment. Therefore, any suspected vulvar lesion arisen during EC follow-up should be biopsied and monitored closely, despite that the vulva represents an unusual metastatic site. Abstract : Supplemental Digital Content is available in the text